Influence of students' attitude on the management of discipline in public secondary schools in Kigumo Sub-County, Muranga County, Kenya - Muiru, Anne Wanjiku (International Journal of Educational Innovation and Research, 2022)
The purpose of this study was to assess the influence of students' attitudes on the management of discipline in public secondary schools in Kiguma Sub County, Muranga County. The study was guided by the Social Learning Theory and System Management Theories. The study adopted a concurrent triangulation design with a mixed design methodology where both qualitative and quantitative methods were employed. The study population were all the public secondary schools in Kigumo Sub County, Muranga County including all the students, teachers and deputy principals. A stratified random sampling method was used to pick 379 students. Purposive sampling was used to pick 30 deputy principals and 30 teachers in charge of discipline management. Questionnaires and interview schedules were used in data collection. The study was piloted in 5 schools in the neighbouring Kahuro Sub County. Statistical Package for Social Sciences (SPSS) was used in data analysis to generate the frequencies, descriptive statistics, cross-tabulation statistics, chi-square tests as well as correlation coefficient statistics that were used to analyze the data and answer the research questions. The study made some important findings that drew it to make some important conclusions. It can be noted that there were significant relationships between school characteristics and issues of indiscipline. In the recommendation, guidance and counselling should be included as part of the secondary school curriculum. Additionally, community centres and rehabilitation centres should set up to take care of students and promote social activities.